STATUS OF WEIGHT CHANGE, LIFESTYLE BEHAVIORS, DEPRESSION, ANXIETY AND DIABETES MELLITUS IN A COHORT WITH OBESITY DURING THE COVID 19 LOCKDOWN.TURK-COM STUDY GROUP - Dilek Yazıcı; Mehmet Mahir Fersahoğlu; Tuba Fersahoğlu; Nuriye Esen Bulut; Hüseyin Çiğiltepe; Özgen Çeler; SEDA Sancak; Cem Sulu; Emre Durcan; Serdar Şahin; Özge Polat Korkmaz; Sıla Hidayet Bozdoğan Polat; et al. (Obesity Facts, 2022)
Introduction: The COVID-19 pandemic led to a lockdown period. Confinement periods have been related to unhealthy lifestyle behaviors. Our study aimed to determine weight change, changes in eating and exercise habits, the presence of depression and anxiety, and diabetes mellitus (DM) status in a cohort of patients with obesity. Methods: The study was undertaken in nine centers of Collaborative Obesity Management (COM) of the European Association for the Study of Obesity (EASO) in Turkey. An e-survey about weight change, eating habits, physical activity status, DM status, depression, and anxiety was completed by patients. The International Physical Activity Questionnaire (IPAQ) score was used to determine physical activity in terms of metabolic equivalents (METs). A healthy nutrition coefficient was calculated from the different categories of food consumption. The Patient Health Questionaire (PHQ-9) and General Anxiety Disorder (GAD-7) were used for determining depression and anxiety, respectively. Results: Four hundred twenty-two patients (age 45±12.7 years, W/M=350/72) were included. The healthy nutrition coefficient before the pandemic was 38.9±6.2 and decreased to 38.1±6.4 during the pandemic (p<0.001). Two hundred twenty-nine (54.8%) patients gained weight, 54 (12.9%) were weight neutral, and 135 (32.3%) lost weight. Patients in the weight loss group had higher MET scores and higher healthy nutrition coefficients compared with the weight gain and weight-neutral groups (p<0.001). The PHQ and GAD scores were not different between the groups. Percent weight loss was related to healthy nutrition coefficient〈CI: 0.884 (0.821-0.951), p=0.001〉 and MET categories 〈CI: 0.408 (0.222-0.748), p=0.004〉. One hundred seventy patients had DM. Considering glycemic control, only 12 (8.4%) had fasting blood glucose <100 mg/dL and 36 (25.2%) had postprandial BG <160 mg/dL. When patients with and without DM were compared in terms of dietary compliance, MET category, weight loss status, PHQ scores, and GAD scores, only MET categories were different; 29 (11.7%) of patients in the nondiabetic group were in the highly active group compared with 5 (2.9%) in the diabetic group. Conclusion: The COVID-19 lockdown resulted in weight gain in about half of our patients, which was related to changes in physical activity and eating habits. Patients with DM who had moderate glycemic control were similar to the general population in terms of weight loss but were less active.